Primary cutaneous follicular helper T‐cell lymphoma. (18th September 2015) - Santonja, Carlos; Soto, Carlos; Manso, Rebeca; Requena, Luis; Piris, Miguel Angel; Rodríguez‐Pinilla, Socorro María
Abstract : Follicular helper T‐cells (TFH) represent a specific subset of CD4‐positive helper T‐cells that help B‐cells to differentiate into long‐lived antibody‐secreting plasma cells or memory B‐cells. The expression of TFH markers in neoplastic T‐cells, traditionally related to the angioimmunoblastic (AITL) subgroup of peripheral T‐cell lymphomas, is nowadays well‐known to be more widespread than previously thought. We report hereby a case of cutaneous T‐cell lymphoma in a 75‐year‐old woman, whose morphological and immunophenotypical features raises the differential diagnosis between cutaneous involvement by AITL and the recently described primary cutaneous T‐cell lymphoma with follicular helper‐phenotype.